Inhibition of glutaminolysis in combination with other therapies to improve cancer treatment. (June 2021) - Shen, Yao-An; Chen, Chi-Long; Huang, Yi-Hsuan; Evans, Emily Elizabeth; Cheng, Chun-Chia; Chuang, Ya-Jie; Zhang, Cissy; Le, Anne
Abstract: Targeting glutamine catabolism has been attracting more research attention on the development of successful cancer therapy. Catalytic enzymes such as glutaminase (GLS) in glutaminolysis, a series of biochemical reactions by which glutamine is converted to glutamate and then alpha-ketoglutarate, an intermediate of the tricarboxylic acid (TCA) cycle, can be targeted by small molecule inhibitors, some of which are undergoing early phase clinical trials and exhibiting promising safety profiles. However, resistance to glutaminolysis targeting treatments has been observed, necessitating the development of treatments to combat this resistance. One option is to use synergy drug combinations, which improve tumor chemotherapy's effectiveness and diminish drug resistance and side effects. This review will focus on studies involving the glutaminolysis pathway and diverse combination therapies with therapeutic implications.